Digital currency and its implications for traditional banking systems: A qualitative inquiry - Usaj, Vesel; Gashi, Kushtrim (The Economics and Finance Letters, 2025)
The purpose of this study is to examine the transformative implications of digital currencies, with a particular focus on cryptocurrencies and central bank digital currencies (CBDCs), for the conventional banking system. The analysis aims to understand how these instruments affect banking operations, consumer trust, regulatory frameworks, and overall financial stability. The study applies a qualitative content analysis to a broad collection of peer-reviewed articles, policy documents, and industry reports. This approach makes it possible to identify recurring themes related to operational impacts on banks, adoption drivers, regulatory and compliance challenges, and macro-level stability concerns. The findings indicate that digital currencies are reshaping bank margins, raising the threat of disintermediation, and fueling shifts in consumer confidence, while regulatory design and policy choices remain critical for safeguarding stability. The evidence shows that the adoption of cryptocurrencies and CBDCs is not only influencing how banks manage payments and deposits but also altering the regulatory environment and competition within financial services. The practical implications of this research suggest that banks must enhance risk management practices, diversify strategies, and adopt a more balanced regulatory approach to survive in the evolving digital financial ecosystem. The study integrates fragmented evidence into a coherent framework that both contributes to theoretical understanding and provides policy recommendations for regulators and practitioners.